Perancangan UI/UX Aplikasi Marketplace Barbershop Menggunakan Metode Design Thinking - Islami, Muhammad Chairuladnan Syaifullah; Wibowo, Nur Cahyo; Afandi, Mohamad Irwan (Universitas Multi Data Palembang, 2024)
A barbershop is a modern hair-cutting service provider that offers more comprehensive facilities compared to traditional barbershops. However, until now, there has not been an application that accommodates various barbershops with a good user interface and user experience. The aim of this research is to design a marketplace application interface for barbershops on an Android-based mobile platform using the design thinking method to achieve good usability. This research will discuss the design of a mobile application interface using the design thinking method. This method focuses on users and products to generate ideas that can meet user needs. The design evaluation phase is conducted in terms of usability using the usability testing method. From a visual perspective, the heuristic evaluation method is used. In this research, two iterations were conducted, resulting in good usability with a score of 77% on the staff side and 80% on the customer side.